ANALISIS BIBLIOMETRIK: TREN COOKIES FUNGSIONAL TAHUN 2015–2025 - Vioni Nurhasanah; Yenni Okfrianti; Kamsiah Kamsiah; Ade Febryanti (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Functional cookies are food products developed not only for taste but also for their added health benefits, utilizing ingredients with bioactive compounds. In response to rising public interest in health and nutrition, this study explores the research landscape on functional cookies from 2015 to 2025. The bibliometric approach is used to understand trends, collaboration patterns, and potential innovations in this field.Objectives: encouraging innovation in the development of healthier and more attractive food products, in addition it is expected to contribute to the formulation of policies, the community presents scientific literature on food and opens opportunities for the local food industry.Methods: This research employed a descriptive bibliometric method using secondary data collected from the database Scopus. A total of 160 scientific articles were selected based on inclusion criteria using the keywords “functional cookies”. Data were processed using VOSViewer version 1.6.18 and R-Studio version 4.3.2 to analyze publication trends, most relevant keywords, prolific authors, collaboration networks, and journal contributions. Result: The analysis reveals a consistent increase in the number of publications related to functional cookies between 2015 and 2025. The most frequent keywords include: functional food, antioxidant, fiber, phenolic compounds, and cookies. The journal Foods contributed the highest number of publications, with 13 documents. The most cited document within this period recorded 85 citations. The most relevant country is India. Functional ingredients used include both conventional and underutilized food sources, such as banana peel, okara, spirulina, and moringa leaves, indicating a trend towards sustainable and innovative food processing.Conclusion: There is a growing global interest in the development of functional cookies as reflected in increasing research publications from 2015 to 2025. Most publications come from developing countries with a high focus on natural and sustainable ingredients. This analysis helps identify gaps in current research and offers direction for future innovation in functional food products.Keywords: Functional cookies; bibliometric analysis; food innovation; functional ingredients ABSTRAKLatar Belakang: Functional cookies merupakan produk pangan yang dikembangkan tidak hanya untuk menghasilkan cita rasa yang baik, tetapi juga memberikan manfaat tambahan bagi kesehatan melalui penggunaan bahan yang mengandung senyawa bioaktif. Seiring meningkatnya kesadaran masyarakat terhadap pola makan sehat, penelitian ini bertujuan mengeksplorasi lanskap dan tren penelitian mengenai functional cookies selama periode 2015–2025.Tujuan: Penelitian ini bertujuan mendorong inovasi dalam pengembangan produk pangan yang lebih sehat dan menarik. Selain itu, hasil penelitian diharapkan dapat berkontribusi dalam penyusunan kebijakan di bidang pangan, memperkaya literatur ilmiah mengenai pangan fungsional, serta membuka peluang bagi pengembangan industri pangan lokal.Metode: Penelitian ini menggunakan metode bibliometrik deskriptif dengan data sekunder yang diperoleh dari basis data Scopus. Sebanyak 160 artikel ilmiah yang memenuhi kriteria inklusi dengan kata kunci